Olahan Daun Kelor Untuk Perbaikan Status Gizi Balita dalam Upaya Pencegahan Stunting - Nurdin, Nasrayanti; Sunandar, Sunandar; Ariyana, Ariyana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Stunting is caused by lack of nutrient intake and chronic infectious diseases. Age. One of the efforts to prevent stunting is to use local plants as food. Moringa plant (Moringa oleifera) is one of the foodstuffs that has a million benefits for health. In South Sulawesi Province, the target has not yet been achieved. This study aims to determine how the effect of processed Moringa leaves to improve the nutritional status of toddlers in an effort to prevent stunting at the Pangkajene Health Center, Sidrap Regency. The research method used is a quasi-experimental research design (Quasy experiment study) using the One group pre and post test design, which is a study by comparing the nutritional status of children under five before the intervention and after the intervention. The sampling technique in this study was taken by consecutive sampling. From the results of the study, it was found that before the administration of processed Moringa leaves there was one toddler who was stunted, while after the administration of processed Moringa leaves all toddlers were in normal nutritional status (TB/U) as many as 30 toddlers. It can be seen that there are differences in the average nutritional status (TB/U) of toddlers before and after the administration of processed Moringa leaves. So it can be concluded that there is a relationship between processed Moringa leaves and efforts to prevent stunting in toddlers at the Pangkajene Health Center, Sidrap Regency.